Pengaruh Audit Internal Terhadap Kinerja Perusahaan pada PT Krakatau Steel (Persero) Tbk - Mutiara Nuru Syifa; Sudradjat Sudradjat (Indonesian Accounting Literacy Journal, 2021)
Company performance is considered successful if they can sustain life, grow and earn profits in each period. To achieve all the ways mentioned, the company must implement continuous monitoring that carried out by internal audit so that the company can realize its objectives and satisfy all interested groups. The survey method is used for this research by administering the questionnaires to 64 respondents from the target population. Descriptive quantitative analysis and simple linear regression analysis were used as data analysis technique. The research data is processed using Microsoft Excel 2016, and IBM Statistics SPSS ver23.0. From the findings, this research concludes that internal audit has a positive relationship with company performance and the influence of the company performance against internal audit is strong that is equal 81% and the remaining 19% influenced by other factors outside the model.